A new species of the genus Iiella Băcescu, 1968 (Crustacea: Mysida: Mysidae) from Malaysia, with notes on I. elegans (Tattersall, 1960) - Fukuoka, Kouki (Zootaxa, 2011)
Iiella malayensis sp. nov. from Malaysian waters is described here. This species is distinguished from related species by the shape of the rostral plate, the number and length of the subsegments of the first exopodal segment of the third male pleopod, the number of spines on the labrum, the number of spiniform setae on the lateral margin of the telson, and the position of the anterior end of the apical cleft of the telson. Supplemental taxonomic notes on I. elegans (Tattersall, 1960) based on type specimens are provided. A key to the species of Iiella is provided.